Dimensions of holistic education in Indian higher education: A LIBRE/EMC²-guided systematic literature review - Brahmi, Mannu; Jain, Harshita; Desai, Anushka; Kumar, Jyoti (Asian Journal of Contemporary Education, 2025)
Recognizing the increasing emphasis on whole-person development, this study investigates key dimensions of holistic education in Indian higher education by integrating philosophical, policy, and literature perspectives. Drawing from contemporary Indian spiritual-philosophical wisdom and policy frameworks such as the National Education Policy 2020 and United Nations Sustainable Development Goal 4.7, the study identifies LIBRE/EMC² as a culturally grounded, neurocognitively informed framework for holistic education in India. A qualitative systematic literature review, conducted in line with PRISMA guidelines, was undertaken using Scopus and Semantic Scholar databases to evaluate the presence of four core LIBRE/EMC² dimensions, empathy, mindfulness, compassion, and critical inquiry, within holistic education literature. Eight original peer-reviewed articles were selected and analyzed using thematic coding and qualitative comparative methods to validate these dimensions. The findings confirm their consistent presence, often linked to themes such as interpersonal sensitivity, lifelong learning, social-emotional competencies, and reflective practice. The review further underscores the institutional and pedagogical need for holistic approaches to foster whole-person development. These insights suggest that culturally sensitive, evidence-based frameworks like LIBRE/EMC² can inform curriculum design, policy implementation, and assessment in India, and potentially beyond. The study calls for developing localized assessment tools and scalable strategies to integrate these dimensions into higher education.